Effects of in vitro digestion and storage on the phenolic content and antioxidant capacity of a red grape pomace. (17th February 2017) - Wang, Shenli; Amigo-Benavent, Miryam; Mateos, Raquel; Bravo, Laura; Sarriá, Beatriz
Abstract: Red grape pomace (RGP) is a major winery by-product with interesting applications due to its high phenolic content and antioxidant capacity. Effects of in vitro gastrointestinal digestion and storage on the phenolic content and antioxidant capacity of RGP were studied. RGP polyphenols were stable under stomach-mimicking conditions and more sensitive to small intestine conditions, reducing anthocyanins and flavonols. After 3- and 6-month storage, at either 4 or 25 °C, there were no changes in the total phenolic and condensed tannin content, or antioxidant capacity (evaluated by ABTS, FRAP, ORAC assays); however, after 9 months these parameters decreased. Contrarily, chromatic b* values were higher, thus the samples had more intense red color, which may be related to the increased condensed tannin content. Storage time or temperature induced no changes in microbiological load. RGP preserves high antioxidant capacity after storage and in vitro digestion and thus presents potential as a functional ingredient or nutraceutical. Graphical Abstract: